Bhārata-darśana, arthāt, Aṅgrezī śāsana ke ārambha se vartamāna samaya taka ke śāsana meṃ Bhāratavāsiyoṃ kī saccī daśā kā varṇana - Bhandari, Sukhsampattirai (SAMP early 20th-century Indian books project, 1921)
History of India.